Effect of low‐level laser therapy on postoperative pain after single‐visit root canal retreatment of mandibular molars: A randomized controlled clinical trial. (29th August 2021) - Fazlyab, Mahta; Esmaeili Shahmirzadi, Sepideh; Esnaashari, Ehsan; Azizi, Arash; Moshari, Amir Abbas
Abstract: Aim: To compare the effect of low‐level laser therapy (LLLT) on postoperative pain after single‐visit root canal retreatment on mandibular molars. Methodology: This randomized controlled clinical trial included 36 patients referred to the Department of Endodontics, Islamic Azad University, Tehran, Iran. Healthy patients who required root canal retreatment on symptomatic first or second mandibular molars, with a PAI index score of 2 or 3, preoperative tooth and percussion pain of <56 mm on a 170‐mm visual analogue scale (VAS) were included. After local anaesthesia using inferior alveolar nerve block followed by rubber dam isolation and access cavity preparation, the D RaCe retreatment system was used to remove the existing root filling material, and after canal negotiation and gaining patency, working length was determined with an apex locator. Further canal enlargement was carried out with size 35, 0.04 taper, and size 40, 0.04 taper RaCe rotary instruments and then canals were filled using laterally compacted gutta–percha points and AH Plus sealer. The patients were randomly assigned to treatment groups: In the LLLT group, a 980‐nm diode laser set at 6.89 W/cm 2 energy density, 0.5 W power, and a tip diameter of 10 mm were activated from the buccal side on the mesial and distal root apices for 15 s. In the sham group, the laser handpiece was placed inside the patient's mouth at the same location, but the laser was not activated. Then patients were instructed to record their postoperative pain levels at 4, 8, 12 and 24 h and 2, 3 and 7 days after treatment on separate VAS scales. For data analysis, the independent sample t and the Mann–Whitney U tests were used. Nominal variables were analysed by using the chi‐square test. Results: In the LLLT group, the most intense pain was reported 24 and 48 h post‐treatment [mean (SD) = 0.22 (0.54) for both], whereas in the sham group, the most intense pain level was observed 4 h post‐treatment [mean (SD) = 0.78 (0.80)]. At the 4‐h interval, pain intensity was significantly lower in the LLLT group ( p  = .016). Conclusions: Low‐level laser therapy reduced postoperative pain after single‐visit root canal retreatment of mandibular molars only four hours following the procedure.